Automatic exchange of information: towards a new global standard of tax transparency - Pecho Trigueros, Miguel Eduardo (2014)
Tax authorities are increasingly relying on mutual cooperation with their foreign peers to enforce more effectively their internal tax laws. After the banking scandals of 2008 and the subsequent global financial crisis, the Global Forum on Transparency and Exchange of Information for TaxPurposes has proposed the exchange of information upon request as the fiscal transparency standard. However, some measures adopted by the European Union, previous initiatives from the Organization for Economic Cooperation and Development (OECD) and, above all, the introduction of the Foreign Account Tax Compliance Act (Fatca) by the United States in 2010 have promoted the need to adopt the automatic exchange of information as the new fiscal transparency standard. Automatic exchange of information allows home countries to verify whether their taxpayers have correctly included foreign income, allowing tax authorities to have early warning of possible noncompliance cases. In February 2014, the OECD published its proposal for a new global model of automatic exchange of financial account information. The new global model contains the necessary legal instruments and due diligence and reporting procedures, mainly for financial institutions.